Antiviral and neuroprotective role of octaguanidinium dendrimer-conjugated morpholino oligomers in Japanese encephalitis. - Arshed Nazmi; Kallol Dutta; Anirban Basu (Public Library of Science (PLoS), 2010)
BACKGROUND: Japanese encephalitis (JE), caused by a mosquito-borne flavivirus, is endemic to the entire south-east Asian and adjoining regions. Currently no therapeutic interventions are available for JE, thereby making it one of the most dreaded encephalitides in the world. An effective way to counter the virus would be to inhibit viral replication by using anti-sense molecules directed against the viral genome. Octaguanidinium dendrimer-conjugated Morpholino (or Vivo-Morpholino) are uncharged anti-sense oligomers that can enter cells of living organisms by endocytosis and subsequently escape from endosomes into the cytosol/nuclear compartment of cells. We hypothesize that Vivo-Morpholinos generated against specific regions of 3' or 5' untranslated regions of JEV genome, when administered in an experimental model of JE, will have significant antiviral and neuroprotective effect. METHODOLOGY/PRINCIPAL FINDINGS: Mice were infected with JEV (GP78 strain) followed by intraperitoneal administration of Morpholinos (5 mg/kg body weight) daily for up to five treatments. Survivability of the animals was monitored for 15 days (or until death) following which they were sacrificed and their brains were processed either for immunohistochemical staining or protein extraction. Plaque assay and immunoblot analysis performed from brain homogenates showed reduced viral load and viral protein expression, resulting in greater survival of infected animals. Neuroprotective effect was observed by thionin staining of brain sections. Cytokine bead array showed reduction in the levels of proinflammatory cytokines in brain following Morpholino treatment, which were elevated after infection. This corresponded to reduced microglial activation in brain. Oxidative stress was reduced and certain stress-related signaling molecules were found to be positively modulated following Morpholino treatment. In vitro studies also showed that there was decrease in infective viral particle production following Morpholino treatment. CONCLUSIONS/SIGNIFICANCE: Administration of Vivo-Morpholino effectively resulted in increased survival of animals and neuroprotection in a murine model of JE. Hence, these oligomers represent a potential antiviral agent that merits further evaluation.